Epistolary Practices of Upper Social Circles in Graeco-Roman Egypt: The Letters of Pecyllus, an (ex-) Gymnasiarch, Prytanis and Bouleutes of Third Century Oxyrhynchus. (M. Dana (ed.), La correspondance privée dans la Méditerranée antique: sociétés en miroir, Scripta Antiqua series, 2023)
This paper is about Pecyllus, a magistrate in 3rd c. AD Oxyrhynchus, whose dossier consists of several private and official documents as well as letters. After a brief description of Pecyllus’ social and financial situation, the paper focuses on his private letters, analysing how Pecyllus adapted the layout, palaeography and linguistic style of each of his letters according to the message, the addressee and situation. It argues that ancient letter writers were able to adapt the external appearance of their writings according to their relationship to the addressee and in order to increase the persuasiveness of their letters.